Etos Kerja Nelayan Di Kelurahan Sawah Luhur, Karangantu Serang, Banten - Marisatu Zahra; Haryono Haryono; Rizki Setiawan (Peneliti.net, 2023)
This research is motivated by the realities of life experienced by the coastal communities of the Sawah Luhur Region, Karangantu Serang, Banten. This research on the work ethic of fishermen in Karangantu was conducted to describe and be able to find out the form of the work ethic of fishing communities to meet their daily needs. Participants or informants in this study were fishermen, communities, and people who own boats. The techniques used in this study were direct observation and interviews with question sheets. Based on observations, the authors report that the work ethic of fishermen has similarities and differences with other coastal communities. The social reality of coastal communities, according to Redifield, corresponds to the reality in the sub-district of Sawah Mulia, Karangantu Serang, Banten.